Glide epenthesis as a repairing strategy of English complex peaks in the Tonga linguistic environment: the distinctive feature paradigm - Zivenge, W. (Midlands State University, 2016)
The paper discusses how epenthesis, as a nativisation process, is applied to English words that enter into the Tonga linguistic environment as borrowings. It is generally the habit of speech communities that when they borrow new words from another language into their own systems, they nativise them to suit the linguistic expectations of their languages. This is because of the fact that there is not any language which is a replica of the other. Languages are unique in as much as the speakers of these languages are. As a result the phonological and morphological systems of languages are different. When new words find their way into another language, they are therefore linguistically remodeled to suit the rules of the receiving languages. One of the processes that can be adopted for this particular purpose is epenthesis. It is therefore the scope of this paper to discuss how English words, borrowed into the Tonga language are nativised, using the epenthetic principles. Only languages that are complete and integral can effectively handle loans. It is also within the framework of this discussion to assert Tonga as a complete and integral language or not, depending on how its speakers handle loans. Tonga borrows words from the English language quite often. The discussion is informed by the Distinctive Feature Theory. The theory enables the author to justify certain epenthetic behaviors that take place on English loans in the process of nativisation by the Tonga native speakers.